An Analysis of Acadmic Research on Shah Abdul Latif Bhitai - Burrio, Hakim Ali (sourcecoder, 2022)
"The Sindh region is significant to Sufi philosophy. The literature and language of Sindhi origin have a long and rich history. In 1689 CE, Shah Latif was born into a Sayyid family. In addition to coming from a well-respected family, Shah Latif also had a higher place in the social class system. Shah Latif, though, denied this idea of social superiority. He distanced himself from these conventional privileges and established relationships with society's underprivileged and marginalized groups. Developing close ties with the public was more important to him than standing with the ruling class or other political elites. This paper critically assesses the scholarly research on Shah Latif by analysing and discussing it”.